Survey of Legionella Species Found in Thai Soil - Tatiana C. Travis; Ellen W. Brown; Leonard F. Peruski; Duangkamon Siludjai; Possawat Jorakate; Prasert Salika; Genyan Yang; Natalia A. Kozak; Maja Kodani; Agnes K. Warner; Claressa E. Lucas; Kathleen A. Thurman; et al. (International Journal of Microbiology)
Members of the Gram-negative genus Legionella are typically found in freshwater environments, with the exception of L. longbeachae, which is present in composts and potting mixes. When contaminated aerosols are inhaled, legionellosis may result, typically as either the more serious pneumonia Legionnaires’ disease or the less severe flu-like illness Pontiac fever. It is presumed that all species of the genus Legionella are capable of causing disease in humans. As a followup to a prior clinical study of legionellosis in rural Thailand, indigenous soil samples were collected proximal to cases’ homes and workplaces and tested for the presence of legionellae by culture. We obtained 115 isolates from 22/39 soil samples and used sequence-based methods to identify 12 known species of Legionella represented by 87 isolates.